INDEXING ENTREPRENEURIAL SUCCESS OF FLORICULTURAL SMALL ENTERPRISES: EVIDENCE FROM SRI LANKA - Kalani Asmitha Kiriveldeniya; P Sivashankar; M S Elapata; R P Mahaliyanaarachchi; M Esham (Socio-Economics/Agribusiness Department, 2020)
Commercialized agriculture shows better avenues in diversifying the rural livelihoods. Floriculture industry is an avenue to initiate successful small scale enterprises in a conductive environment. This paper explores the aspects in small scale floriculture industry to adapt strategies in rural development through indexing the success of floriculture small enterprises under eight dimensions. Both interviewer administrated questionnaire and in-depth interviews with key respondents were adapted in data collection. Findings indicate that average entrepreneurial success index of the sample is 0.57, meaning average success level and 38% were very successful. Diversification (0.78), profitability (0.68), social recognition (0.61) are the dimensions that have highest mean values and quality of supply or service (0.56), customer satisfaction (0.45) and employee satisfaction (0.27) had lower mean values. Middle age (34%) and women (64%) entrepreneurs’ engagement in the industry was high. Time spent on the enterprise and labour usage depends on whether the business is their primary or secondary income activity. Floriculture small scale enterprises have been identified as a good income avenue for middle aged women in rural areas. However, rural development strategies need to address the requirement of how to develop the management skills of rural entrepreneurs as well for the sustainability of their enterprises.